2011
DOI: 10.1063/1.3656718
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characteristics of Dy3+ doped Y3Al5O12 transparent ceramics

Abstract: The spectroscopic characteristics of Dy3+ in YAG (Y3Al5O12) transparent ceramics prepared by solid state synthesis were investigated, with special attention to the visible (yellow, blue) emissions that could be pumped directly by the new developed blue–violet or near UV laser diodes. The absorption and emission spectra, recorded at different temperatures from 10 to 300 K, were analyzed and relevant new parameters, improved energy level scheme, temperature effects, intensity parameters based on Judd-Ofelt theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 46 publications
0
21
1
1
Order By: Relevance
“…Copyright 2011 Author(s (YAG) are widely used as host materials for transition and rare earth elements for laser, optoelectronic and scintillation applications. [1][2][3][4][5][6][7] They are the most important solid state laser host materials and the most promising scintillation materials. In addition to their technological importance, they possess many interesting optical properties.…”
mentioning
confidence: 99%
“…Copyright 2011 Author(s (YAG) are widely used as host materials for transition and rare earth elements for laser, optoelectronic and scintillation applications. [1][2][3][4][5][6][7] They are the most important solid state laser host materials and the most promising scintillation materials. In addition to their technological importance, they possess many interesting optical properties.…”
mentioning
confidence: 99%
“…2.0 Â 10 À21 cm 2 for the p and r polarizations) [23]. As already noted previously [9][10][11], the 6 H 15/2 ? 6 F 11/2 transition centered at 1300 nm is considered to be hypersensitive, which can be strongly influenced by the surrounding environment around Dy 3+ .…”
Section: Methodsmentioning
confidence: 87%
“…The low pumping efficiency, which raises the laser threshold and reduces the laser slope efficiency, seems so far be the most probable obstacle to realize efficient yellow output, not only for the title crystal but also for nearly all Dy 3+ -doped materials. Some measures to enhance absorption efficiency have been discussed in detail in a recent paper [9]. Comparatively large crystal length is required to increase the pump absorption.…”
Section: Evaluation Of Yellow Laser Potentialmentioning
confidence: 98%
See 1 more Smart Citation
“…Dy 3? doped LnAG luminescent materials were reported by many researchers [4,[9][10][11][12][13][14]. Previous studies showed that the characteristics emission intensity of Dy 3?…”
Section: Introductionmentioning
confidence: 98%